Cyclical time and instant in One Hundred Years of Solitude - Másmela Arroyave, Carlos (Estudios de Filosofía, 2011)
The eonic passing of time draws a destiny marked by the impossibility of adjusting to the chronological sequence of time, and the frustration and the fear of the Buendía lineage reflect their impotence to experiment a decisive and kairological time which deviates from the chronological one. The said destiny is like a Maelström that progressively wears out and deteriorates on its axis until it reaches catastrophe. The blunder of man is evidenced due to the lack of the propitious occasion that would correspond to the case of an opportunity, when Macondo is devastated by the wearing-out of the axis. Its devastation, imperceptible just in the chaotic moment of the instant, enables one, at the same time, to make out the total suppression of man´s power to be.